Quantitative proteomic characterization of human sperm cryopreservation: using data-independent acquisition mass spectrometry - Fu, Longlong (BMC Urol, 2019)
BACKGROUND: Human sperm cryopreservation is a simple and effective approach for male fertility preservation. METHODS: To identify potential proteomic changes in this process, data-independent acquisition (DIA), a technology with high quantitative accuracy and highly reproducible proteomics, was used to quantitatively characterize the proteomics of human sperm cryopreservation. RESULTS: A total of 174 significantly differential proteins were identified between fresh and cryoperservated sperm: 98 proteins decreased and 76 proteins increased in the cryopreservation group. Bioinformatic analysis revealed that metabolic pathways play an important role in cryopreservation, including: propanoate metabolism, glyoxylate and dicarboxylate metabolism, glycolysis/gluconeogenesis, and pyruvate metabolism. Four different proteins involved in glycolysis were identified by Western blotting: GPI, LDHB, ADH5, and PGAM1. CONCLUSIONS: Our work will provide valuable information for future investigations and pathological studies involving sperm cryopreservation.